Adherence to Antifungal Guidelines in Malignant Hematology Patients: A Review of the Literature. (December 2019) - Reslan, Zainab; Lindsay, Julian; Kerridge, Ian; Gellatly, Rochelle
Objective: To review the published literature assessing adherence rates to antifungal guidelines and reasons for nonadherence in the adult malignant hematology inpatient setting.Data sources: The databases Embase, MEDLINE, and PubMed (from data inception to May 2019) were searched using the terms hematology, oncology, antifungal, guidelines, adherence, and stewardship with the search limited to adult human subjects and published in English. This yielded 123 articles. From this list, studies that were published in peer-reviewed journals were extracted, leaving 10 citations that met the final inclusion criteria.Study Selection and Data Extraction: Ten studies were selected assessing adherence to consensus antifungal guidelines in the malignant hematology setting. These included studies investigating the introduction of antifungal stewardship programs in tertiary hospitals.Data Synthesis: Although the studies were heterogeneous, all focused on appropriateness of antifungal therapy in the inpatient setting. Adherence to antifungal guidelines for optimal antifungal prophylaxis and treatment was low in most studies, with rates of inappropriate antifungal therapy ranging from 25% to 70% of fungal prescriptions.Relevance to Patient Care and Clinical Practice: Adherence rates with guidelines for antifungal therapy are low in the hematology inpatient setting. This may affect infection rates influencing morbidity and mortality in this high-risk population.Conclusion: Given the prevalence of invasive fungal infections in malignant hematology inpatients, suboptimal adherence with antifungal guidelines is concerning. This demands a focus on education, antifungal stewardship, and updating guidelines to meet real-world scenarios. Adherence with antifungal guidelines in the outpatient hematology setting is unknown and requires further research.